A SEMIOTIC STUDY ON VERBAL AND VISUAL SIGNS FOUND IN REVLON COSMETICS ADVERTISEMENTS - Rika, Ni Wayan; Suastini, Ni Wayan; Pratiwi, Desak Putu Eka (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The aims of this research are to identify and analyze the meaning of verbal and visual signs found in Revlon cosmetic advertisements. Data of this research are advertisements downloaded from the internet at www.google.com. The theory of semiotics by Saussure (cited in Chandler 2007) was used to analyze verbal and visual signs through signifier and signified, while the theory of semiotics by Barthes (1977) was used to describe the meaning of verbal and visual signs, both denotative and connotative meanings. The theory of the meaning of color also supports this analysis by Cerrato (2012) which is applied to analyze color choices in advertisements. The data were analyzed by descriptive qualitative method and the results of this study showed that there were six verbal signs and six visual signs in two Revlon cosmetic advertisements. These verbal and visual signs have denotative and connotative meanings, where denotative meaning focuses on conveying information related to the advertised product and connotative meaning focuses on conveying other meanings and hidden messages from advertisements to be conveyed to customers, especially women.